2022
DOI: 10.3390/coatings12091233
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Dynamic Load Allowance of the Negative Bending Moment in Continuous Girder Bridges by Weighted Average Method

Abstract: Accurate acquisition of dynamic load allowance (DLA) based on measurement data is essential to the safety assessment of a bridge. When static load tests cannot be achieved, and filtering fails, the estimated DLAs from the experimental method vary widely due to the choice of a left or right band. In this paper, the proposed weighted average method (WAM) is used to possibly solve the above problem in continuous gird bridges. Two-span and three-span precast concrete box-gird bridges were selected to optimize inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

3
0

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…The vehicle crossed the bridge with an unevenness of grade C at a constant speed of 72 km/h. The dynamic displacements of the girder and SWSS are obtained by vehicle-bridge interaction (VBI) [56], and then the DLAs are calculated by Equation (9). The dynamic displacements of the SWSS are determined by the vertical dynamic displacement of the material mass point in the system.…”
Section: Dynamic Responses and Dlasmentioning
confidence: 99%
“…The vehicle crossed the bridge with an unevenness of grade C at a constant speed of 72 km/h. The dynamic displacements of the girder and SWSS are obtained by vehicle-bridge interaction (VBI) [56], and then the DLAs are calculated by Equation (9). The dynamic displacements of the SWSS are determined by the vertical dynamic displacement of the material mass point in the system.…”
Section: Dynamic Responses and Dlasmentioning
confidence: 99%
“…At a speed of 120 km/h, the dynamic response amplitude of the bridge reaches its maximum value. Studies have shown that the influence of vehicle speed on the dynamic response of bridges is relatively complex and may work in conjunction with various other factors to affect the vibration response of the bridge [36].…”
Section: Vehicle Speedmentioning
confidence: 99%
“…Similar findings were also reported by other researchers [ 22 , 25 , 26 , 27 ]. In dynamic load tests, the acquired signals are usually filtered and de-noised, resulting in the removal of higher-order signals [ 16 , 28 ]. Currently, there is no consensus on the cut-off modes for calculating the DAFs of continuous girder bridges [ 29 ].…”
Section: Introductionmentioning
confidence: 99%